Fabrication and characterization of Al/LiCdO/p-Si optical sensor - Cavas, Mehmet (Indian Assoc Cultivation Science, 2022)
In this study, the sol-gel spin-coating method was used to produce pure CdO and 0.1% Li-doped CdO thin films. The main purpose of the study was to investigate the influence of the Li-doping ratio on the photoresponse of CdO thin film. Within this scope, pure CdO and Li-doped CdO chemical solutions were prepared and then deposited onto p-Si wafer and microscope glass as a thin film. Then, the surface morphology and photoresponse properties, etc. of the thin films were investigated. First, the morphological structure of the thin film was studied, and the roughness and size of the thin films were determined. Second, the photoresponse of the thin films was studied in order to determine the optical properties. In determining the photoresponse of the thin films, the films were studied and the transient photocurrent measured under both dark conditions and different luminous intensities. The ideality factor and barrier height parameters of the thin films were calculated as 3.5 and 0.81 eV, respectively. Finally, the capacitance-voltage (C-V), interface state density (D-it), conductance-voltage (G-V), and serial resistance (Rs) were studied at different frequencies. The obtained results showed that the Li-doping ratio changed the electrical and optical properties of the CdO thin film. This finding confirms that using different percentage Li-doping ratios, both the optical and electrical properties of CdO could be changed and improved for use in optoelectronic devices, either as a photodiode or as a photodetector.
Keywords: Nanomaterials; Photodetector; Photodiode; Thin film; CdO film